Meningkatkan Perilaku Prososial Anak Usia 5-6 Tahun Menggunakan Kinds Rubber Rope Games (KIORROGA) di TKQ Salsabila Karawang - Haliza Syahnurmala; Rina Syafrida; Ine Nirmala; Ega Trisna Rahayu (Jurnal Ilmiah Wahana Pendidikan, 2022)
Based on the initial observations made by the authors regarding the problems contained in TKQ Salsabila, namely the prosocial abilities of children aged 5-6 years who have not been able to take turns playing, sharing, and helping peers and teachers in the classroom. From the above phenomenon to improve children's prosocial skills, the author develops media innovation through Kinds Rubber Rope Games (KIORROGA). Kinds Rubber Rope Games aims to provide a choice of media variations made from rubber bands that can also train children's fine motor skills. This study uses an experimental method through the design of The One-Group Pretest-Posttest Design (Arikunto, 2010) with a sample of elementary school students in the Early Childhood category at the age of Kindergarten B1 (n = 19) determined based on Cluster Random Sampling conducted for 8 meetings in group B TKQ Salsabila. The results showed that Kinds Rubber Rope Games (KIORROGA) media. effective in improving the prosocial abilities of children in Salsabila Kindergarten